Wdrożenie elementów Lean Management na przykładzie firmy P.P.U.H "BISS" - Skowroński, Krzysztof (My University, 2012)
Niniejsza praca jest teoretyczno-praktycznym przedstawieniem problematyki optymalizacji produkcji w P.P.U.H „BISS”. Nieefektywne wykorzystanie mocy produkcyjnych, marnotrawstwo posiadanych zasobów prowadzi do obniżenia rentowności przedsiębiorstwa. Podjęcie procesów optymalizacji produkcji wypływa na poprawę organizacji przedsiębiorstwa, wyników finansowych firmy, lepszą jakość oferowanych produktów.

This thesis is the theoretical and practical presentation of optimize production in P.P.U.H “BISS” company. Inefficient capacity, waste of resources leads to a reduction in the profitability of the company. Take the optimization process flows to improve the production organization of the business's financial performance, better quality of products.
Implementation of the Lean Management components on the example of P.P.U.H “BISS”
Keywords: lean management; optymalizacja; produkcja; lean management; optimize; production